2017
DOI: 10.1016/j.acap.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physician Implicit Racial Bias Toward Adults Versus Children

Abstract: Background and Objectives The general population and most physicians have implicit racial bias against black adults. Pediatricians also have implicit bias against black adults, albeit less than other specialties. There is no published research on the implicit racial attitudes of pediatricians or other physicians towards children. Our objectives were to compare implicit racial bias towards adults versus children among resident physicians working in a pediatric emergency department (ED), and to assess whether bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 41 publications
7
72
0
Order By: Relevance
“…18 Another recent study found that resident physicians had implicit racial bias against African American children that was similar to levels of bias against African American adults. 19 This emerging body of work indicates that being a child does not protect against the experience of implicit bias.…”
mentioning
confidence: 99%
“…18 Another recent study found that resident physicians had implicit racial bias against African American children that was similar to levels of bias against African American adults. 19 This emerging body of work indicates that being a child does not protect against the experience of implicit bias.…”
mentioning
confidence: 99%
“…2,3 Yet, despite the recognition that harboring bias, stereotypes, and negative attitudes (prejudice) can be a significant barrier to effective patientcentered care, many studies have reported on the pervasiveness of these affects among health care practitioners. [4][5][6][7][8][9][10][11] One significant area of concern is the startling prevalence of obesity bias within the allopathic medicine health care community. [12][13][14][15][16][17][18][19][20][21][22] The present study investigated whether this same bias was also commonplace among members of the complementary and integrative medicine (CIM) community.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, children whose parents had limited English language proficiency had their pain assessed less frequently during postsurgery care and experienced greater pain levels before receiving analgesic medication [32]. And a growing body of research demonstrates that physicians and other health care professionals exhibit implicit (i.e., unconscious) biases based on race [33,34]. To actively combat unconscious bias in pain management and other aspects of trauma-informed pediatric care, professionals can take concrete steps such as acknowledging their own susceptibility to implicit bias and practicing taking the perspective of stigmatized groups; there is empirical support for at least short-term reductions in implicit bias based on these steps [35].…”
Section: Practice Standards and The Ethical Case For Trauma-informed mentioning
confidence: 99%